2020
DOI: 10.1111/acel.13123
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan of long‐lived growth hormone receptor knockout mice was not normalized by housing at 30°C since weaning

Abstract: Growth hormone receptor knockout (GHRKO) mice are remarkably long‐lived and have improved glucose homeostasis along with altered energy metabolism which manifests through decreased respiratory quotient (RQ) and increased oxygen consumption (VO2). Short‐term exposure of these animals to increased environmental temperature (eT) at 30°C can normalize their VO2 and RQ. We hypothesized that increased heat loss in the diminutive GHRKO mice housed at 23°C and the consequent metabolic adjustments to meet the increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Accordingly, the long-lived GHRKO and Ames mice exhibit improved glucose homeostasis and energy metabolism evidenced by decreased respiratory quotient (RQ) and increased oxygen consumption (VO 2 ). In contrast, bGH mice, with high GH/IGF-1 levels show decreased VO(2) and increased RQ [30,32,33]. Taken together, these animal models suggest that diminished GH/IGF-1 activity improves mitochondrial flexibility and increases the capacity for fat oxidation.…”
Section: Gh/ Igf-1 Effects On Mitochondrial Respiration and Atp Produmentioning
confidence: 92%
See 2 more Smart Citations
“…Accordingly, the long-lived GHRKO and Ames mice exhibit improved glucose homeostasis and energy metabolism evidenced by decreased respiratory quotient (RQ) and increased oxygen consumption (VO 2 ). In contrast, bGH mice, with high GH/IGF-1 levels show decreased VO(2) and increased RQ [30,32,33]. Taken together, these animal models suggest that diminished GH/IGF-1 activity improves mitochondrial flexibility and increases the capacity for fat oxidation.…”
Section: Gh/ Igf-1 Effects On Mitochondrial Respiration and Atp Produmentioning
confidence: 92%
“…Taken together, these animal models suggest that diminished GH/IGF-1 activity improves mitochondrial flexibility and increases the capacity for fat oxidation. Interestingly, a recent study found that housing the GHRKO mice at thermoneutral temperature (30 • C) resulted in decreased expression of thermogenic genes in brown adipose tissue (BAT) and elevated core body temperature [32]. However, these mice still maintained their extended longevity phenotype at 30 • C [32], suggesting an intrinsic advantage of mitochondrial function in the GHRKO mice.…”
Section: Gh/ Igf-1 Effects On Mitochondrial Respiration and Atp Produmentioning
confidence: 99%
See 1 more Smart Citation
“…However, daf-2 mutant animals are resistant to age-related decline and long lived [88][89][90]. Consistently, even though GH receptor knockout (GHRKO) mice have increased fat mass and decreased lean mass, they show improved insulin sensitivity and are long lived [91]. Therefore, to establish an informative model of DIO in C. elegans, it is critical to test whether the increase in fat levels correlates with detrimental effects on health.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…We are currently investigating the effect of long-term exposure to different eTs on aging-sensitive traits and longevity of wild-type and GH-mutant mice. We have recently reported that life-long exposure to increased (thermoneutral) temperature does not eliminate the longevity advantage of GH-resistant Ghr-/- mice [ 34 ].…”
Section: Energy Metabolism Is Associated With Extreme Longevitymentioning
confidence: 99%